Analisis Kodikologi dan Tekstologi Manuskrip Mushaf Al-Qur’an Mbah Syatawi Kudus: Aspek Kodikologi dan Aspek Tekstologi: Codicological and Textological Analysis of the Mbah Syatawi Kudus Qur'an Manuscript: Codicological and Textological Aspects - Ahmad Bagas Satriyo; Aziizatul Khusniyah (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2025)
This study examines the codicological and textological aspects of the mushaf Al-Qur’an manuscript of Mbah Syatawi with the aim of understanding its physical characteristics, writing techniques, and the use of rasm, qira`at, scholia, and syakl. This research uses a qualitative approach, using field research methods that focus on collecting primary data through structured interviews with sources directly related to the manuscript, field observations, and digital documentation. The main focus of the research is the manuscript belonging to Mbah Syatawi. The codicological approach is used to analyze the physical aspects of the manuscript such as materials, ink, and illumination, while the textological approach focuses on the writing rules, rasm mushaf (script style), and the qira`at tradition followed. The results show that the manuscript consists of two collections estimated to be over a century old. The inks used are varied, with black ink as the primary color for the Qur’anic text, red ink for scholia and diacritical marks (syakl), and other colors applied to illuminations found on the beginning, middle, and end pages. In terms of writing style, the manuscript employs a mixed rasm combining rasm imla’i and rasm ‘usmani, particularly in the application of rules such as al-Hazf, al-Ziyadah, hamzah, al-Ibdal, and al-Fasl wa al-Wasl. Regarding qira`at, the manuscript follows the qira`at of Imam 'Asim through the transmission line of Imam Hafs. These findings enrich the study of classical mushaf manuscripts in Indonesia, providing significant contributions to preservation efforts, philological studies, and the faithful reproduction of historical manuscripts.